Metalinguistic filters within the bilingual language faculty : a study of young English-Chinese bilinguals - Ong, Kenneth Keng Wee. (2010)
This study reports two metalinguistic parameters that constitute the schematic control of lateral inhibitory links between translation equivalents within the bilingual lexico-semantic system of Green’s (1998a,1998b,2007) inhibitory control (IC) model. Building on Green’s postulation that the bilingual lexico-semantic system is controlled by a hierarchy of schemas under a supervisory attentional system, the bilingual unconsciously filters activated lemmas during fluent spontaneous codeswitching, such that lemmas that are semantico-syntactically versatile or morphosyntactically transparent are likely to reach a threshold of activation first while other lemmas are inhibited. To investigate the issue, we collected code-paired naturalistic and elicited data with a focus on code-switched determiner phrases from 140 Mandarin-English simultaneous bilinguals who were post-secondary students in Singapore. We found that the semantico-syntactic and morpho-syntactic dissimilarities between Mandarin and English activated both filters. As most Mandarin determiners are economical vis-à-vis their English counterparts, their lemmas were selected frequently while English lemmas were largely inhibited. It was also found that our participants preferred English nouns in filling the lexical category for their interpretable feature of number, a feature that is normally absent in Mandarin nouns.